Amelia Earhart : legendary aviator - Haugen, Brenda (Compass Point Books, 2007)
Tells the life story of early-twentieth-century pilot Amelia Earhart, discussing her Midwestern childhood, her beginnings as an aviator, her historic first transatlantic flight, her marriage, and her disappearance.